Belanja Impulsif dalam Penggunaan Paylater : Peran Kepercayaan dan Persepsi Risiko - Novid Kasnanda Putri Ndruru; Ray Octafian (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Rapid growth of paylater services in Indonesia has raised concerns regarding impulsive buying behavior, particularly among students who face financial constraints but demonstrate a high level of digital technology adoption. This study aims to: (1) analyze the effect of trust on the impulsive buying behavior of students at LPK Kartika Bawen Semarang in using paylater services; (2) analyze the effect of risk perception on impulsive buying behavior; and (3) analyze the simultaneous effect of trust and risk perception on students’ impulsive buying behavior. A quantitative approach with a causal associative research design was employed in this study. The sampling technique used was purposive sampling targeting active students who had used paylater services within the last six months. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using multiple linear regression with the assistance of SPSS version 24. The results indicate that trust has a positive and significant effect on impulsive buying behavior, while risk perception has a negative and significant effect. Simultaneously, both variables have a significant effect with a coefficient of determination (R²) of 0.328. Trust was identified as the dominant factor with a standardized beta value higher than that of risk perception. These results indicate that high trust in paylater services reduces psychological barriers to transactions, thereby encouraging spontaneous purchases, while risk perception serves as an inhibiting mechanism that activates cognitive evaluation before decision-making. These findings imply that trust functions as a catalyst for impulsive buying through the consumer decoupling effect, suggesting the need to strengthen digital financial literacy that balances trust development and risk awareness among student paylater users.